1988
DOI: 10.1002/j.2050-0416.1988.tb04600.x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Strain and the Formation of Flavour Components in Cider

Abstract: Two apple juices were fermented at 8°C and 18°C using thirteen strains of Saccharomyces uvarum. Glucose, fructose, malic, lactic, isobutanol, 2-3 butanediol, isoamyl alcohol, ethyl acetate and titratable acidity were determined in the two resulting experimental ciders. This data was correlated by means of multiple regression equations derived from earlier work with the following organoleptic characteristics: sweetness, sourness, fruity, scented, sharp and irritating flavours and a "global hedonlc score" for ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Under the experimental conditions used, it was found that when the fermentation temperature increased, the final concentration of ethyl acetate and some of the higher alcohols decreased (for 1-propanol, 2-methyl-1-propanol and 1-butanol), while 2-and 3-methyl-1-butanol kept similar patterns, as well as ethanol. In a previous study 11 it has been reported that an increase in cider fermentation temperature (from 8°C to 18°C) induced an increase in the amount of 2-methyl-1-propanol and 2-and 3-methylbutanol and a decrease in 1-propanol.…”
Section: Effect Of Temperature With Simultaneous Inoculation Of Micromentioning
confidence: 89%
“…Under the experimental conditions used, it was found that when the fermentation temperature increased, the final concentration of ethyl acetate and some of the higher alcohols decreased (for 1-propanol, 2-methyl-1-propanol and 1-butanol), while 2-and 3-methyl-1-butanol kept similar patterns, as well as ethanol. In a previous study 11 it has been reported that an increase in cider fermentation temperature (from 8°C to 18°C) induced an increase in the amount of 2-methyl-1-propanol and 2-and 3-methylbutanol and a decrease in 1-propanol.…”
Section: Effect Of Temperature With Simultaneous Inoculation Of Micromentioning
confidence: 89%
“…Apple wine, also called cider in some areas, is a popular alcoholic apple beverage in Europe, North America and Australia (Madrera and others ). The flavor of apple wine has an extremely complex chemical pattern in both qualitative and quantitative terms (Williams ; Leguerinel and others ). The volatile aroma compounds of apple wine are closely associated with the type and concentration of aromatic compounds derived from apples, the fermentation process, and the storage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of higher alcohols is temperature dependent, so that changes in temperature may cause changes in the availability of fusel alcohols that are necessary for ester formation (Calderbank and Hammond ). To our knowledge, for apple wine, the parameters that have been studied for their influence on major volatile compounds are mainly focused on yeast types, SO 2 dosage, initial nitrogen content, aging time, juice processing methods, and so on (Leguerinel and others ; Herrero and others ; Wilson and others ; Choi and Nielsen ; Valles and others ; Peng and others ; Kelkar and Dolan ), and the effects of fermentation temperature on the concentration of aromatic compounds and sensory properties of apple wine have been less studied (Herrero and others ).Therefore, it is very important to understand the effects of fermentation temperature on volatile aroma compounds, especially the key compounds that could have a great aromatic impact on apple wines, for improving both the processing technique and final product quality.…”
Section: Introductionmentioning
confidence: 99%
“…The most important volatile compounds formed during fermentation that affect the organoleptic characteristics of cider are higher alcohols, esters, and carbonyl compounds. The formation of aroma in cider depends largely on the yeast species involved in the fermentation (Leguerinel et al ., ; Beech, ).…”
Section: Introductionmentioning
confidence: 99%